2009
DOI: 10.1055/s-0029-1242033
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Platelet-Rich Fibrin Matrix in Facial Plastic Surgery

Abstract: Platelet concentrates enjoyed some clinical popularity in facial plastic surgery several years ago. However, interest waned due to expense, amount of blood required, equipment, space, and staff needed, and lack of clinically significant benefit. A novel, simple method of preparing an autologous platelet derivative (Selphyl; Aesthetic Factors, Princeton, NJ) allows rapid and inexpensive generation of a platelet-rich fibrin matrix (PRFM) that can be used to enhance healing after facial procedures as well as to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
76
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(79 citation statements)
references
References 16 publications
0
76
0
1
Order By: Relevance
“…Although the optimal PRP platelet concentration is unclear, the current method by which PRP is prepared is reported to involve 300-700% enrichment, with high platelet concentrations. [1] Owing to these high concentrations of growth factors, PRP has been used successfully in periodontal therapy, maxillofacial surgery, orthopedics, and sports medicine and recently, PRP has attracted attention in the field of dermatology.…”
mentioning
confidence: 99%
“…Although the optimal PRP platelet concentration is unclear, the current method by which PRP is prepared is reported to involve 300-700% enrichment, with high platelet concentrations. [1] Owing to these high concentrations of growth factors, PRP has been used successfully in periodontal therapy, maxillofacial surgery, orthopedics, and sports medicine and recently, PRP has attracted attention in the field of dermatology.…”
mentioning
confidence: 99%
“…Princeton, New Jersey) to process 18 cc of peripheral blood. Recent studies have shown excellent results when autologous fat is combined with PRP in aesthetic plastic surgery (73,74,75). In order to increase the potential for autologous fat graft acceptance and retention we mix the harvested fat with the autologous PRP in a 4:1 ratio.…”
Section: Fat Preparationmentioning
confidence: 99%
“…The application of PRF in fields of plastic surgery 13 , oral and maxillofacial surgery 14 and implant surgery 15 has demonstrated successful and rapid results in terms of bone regeneration. The field of Periodontal therapy, although, has just begun to explore the vast benefits of PRF.…”
Section: Introductionmentioning
confidence: 99%